Vital Capacity in Different Body Postures among Medical Students - Ghimire, Nisha; Mukhopadhyay, Soumitra (Medical Journal of Eastern Nepal, 2023)
Background: Cross legged sitting posture (sukhasana, yogic) is normal sitting posture in India, Nepal and some neighboring countries. This posture is also claimed to deepen breath. However, not many studies have been documented to observe if there is any difference in vital capacity (VC) of lungs in standing, sitting erect posture in chair, and sitting erect in crossed legged posture. So, our aim is to compare the vital capacity in standing, sitting erect posture in chair, and crossed legged sitting posture. Methods: Forty medical and paramedical students (20 males and 20 females) of Nobel medical college were selected for the study. After selecting the students as per selection criteria, vital capacity was measured with spirometer in standing, sitting erect on chair (palms facing up and down) and sitting erect in crossed legged posture (palms facing up and down). One way ANOVA followed by post hoc analysis was done to compare the vital capacity among different postures. Data were expressed as Mean ± SD. p value <0.05 was considered significant. Results: Significant decrease in vital capacity was observed when posture changed from standing to erect sitting posture (sitting with palms facing up), (2242.50ml ±155.830 vs 2095.0ml± 181.29) p=0.05 in females only. No significant changes were seen between erect sitting posture and crossed legged sitting posture in both palms facing up and down conditions. Conclusion: Vital capacity was highest in standing posture and lowest in erect sitting posture with palms facing up only in females. Though statistically not significant, among sitting postures, the vital capacity was high in crossed legged posture compared to sitting erect in chair in both males and females.